2008
DOI: 10.1108/17465729200800024
|View full text |Cite
|
Sign up to set email alerts
|

Using therapeutic board games to promote child mental health

Abstract: This article focuses on group work with children using a board game format. Combining the principles of group work and board games helps to engage and motivate children and adolescents to address and work through their difficulties. Lifegames are a series of six therapeutic board games developed for group work with children and adolescents who encounter adversity in their life as a consequence of bereavement, family break up, poor relationships, bullying, chronic illness or obesity. The games facilitate the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Previous research (Neistadt et al . ; Streng ; Pon ; Collins & Griess ) has used board games to elicit learning, emotional regulation and attitude change, but not in an intellectual disability or HR context. As such, the results are unique in the HR research arena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research (Neistadt et al . ; Streng ; Pon ; Collins & Griess ) has used board games to elicit learning, emotional regulation and attitude change, but not in an intellectual disability or HR context. As such, the results are unique in the HR research arena.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers (Neistadt et al . ; Streng ; Pon ; Collins & Griess ) have also suggested that board games may be useful for educational purposes, encouraging self‐reflection and discovery (Caballero‐Coulon et al . ), expressing emotions about a topic, discussing issues and concerns, facilitating understanding and disclosure, and ultimately positively changing attitudes and beliefs about sensitive topics (Van der Stege et al .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst, surprisingly, limited research on adult play has been conducted (Vleet & Feeney, 2015 ) several studies exist which explore the use of ‘serious play’ - a term originally coined by researchers using LEGO for learning (Roos et al, 2004 ). Board games have been used in some serious play studies, (Boghian et al, 2019 ; Gauthier et al, 2019 ; Lennon & Coombs, 2007 ; Streng, 2009 ; Struwig et al, 2014 ; Uy, 2019 ) and show potential to stimulate positive emotions and foster connection, factors which are negatively affected by the experience of lockdown. Group play has also been shown to facilitate self-disclosure (Betcher, 1981 ), which in adult learning environments can help facilitate synthesis of learning – a process Baker et al describe as “conversational learning” ( 2005 , p.412).…”
Section: Literature Reviewmentioning
confidence: 99%